2010
DOI: 10.1007/s00276-009-0618-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the pneumatization of the mastoid air cells and paranasal sinuses using three-dimensional reconstruction of computed tomography scans

Abstract: This study examined whether a similarity in pneumatization exists between the mastoid air cells and PNS of individuals; these results may be useful in understanding the normal and pathological conditions of both structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 11 publications
6
59
1
1
Order By: Relevance
“…A positive correlation noted between the pneumatization of mastoid air cells and that of the sphenoid sinus in our study similar to another study [15]. This correlation may be explained by the close proximity of the openings of these structures into the nasal cavity, thus they might expose to the same driving forces that control pneumatization process or other pathological events.…”
Section: Sphenoid Sinus Pneumatizationsupporting
confidence: 89%
“…A positive correlation noted between the pneumatization of mastoid air cells and that of the sphenoid sinus in our study similar to another study [15]. This correlation may be explained by the close proximity of the openings of these structures into the nasal cavity, thus they might expose to the same driving forces that control pneumatization process or other pathological events.…”
Section: Sphenoid Sinus Pneumatizationsupporting
confidence: 89%
“…However, the protrusions don't appear in all cases. The prevalence of the protrusions is quite variable, which may affect the success of transsphenoidal endoscopic surgery [6,[8][9][10][11][12][13]. The prevalence of protrusion of ICA is not conclusive, ranging from 5.2% [14] -32.8% [15], 48.5% [16] and 67.7% [8], depending on the degree of individual pneumatization and the definition used in each study.…”
Section: The Relationship Between Ss Volume and Transsphenoidal Surgimentioning
confidence: 99%
“…Moriguchi (1989) observed a significant difference, with male maxillary sinus volume measuring 17.8 cm 3 and females measuring 15.0 cm 3 , based on CT exams taken for diagnosis of head injuries in 72 cases averaging 42 years old. Kim (2010) et al found that male sinus volume was significantly larger than female sinus volume, based on measurements of maxillary sinus volume using three-dimensional construction processing of CT imagery. Ariji (1994) performed CT image measurements on 115 subjects with an average age of 46.8 years and found that, while males measured 15.40 cm 3 and females measured 13.98 cm 3 , indicating a sex difference, that difference was not statistically significant.…”
Section: Unilateral Maxillary Sinus Volume and Sex Differencesmentioning
confidence: 99%